Virtual Network Embedding Algorithms for Integrated Space-Terrestrial Network - Jiarui FANG; Tingting ZHANG; Yubo ZHAO; Nan WU; Bei LIANG (天地一体化信息网络)
Within the intricate environment of integrated space-terrestrial network, VNE algorithms face novel challenges due to the high variability in user demands, stringent limitations of heterogeneous resources, expansive spatiotemporal scales, and the dynamic nature of network topologies.In light of this, scholars worldwide have delved deeply into the VNE issues pertaining to these networks.This review firstly summarized the three core challenges faced by VNE in these networks based on their characteristics.It then elucidated the current state of research from two major perspectives: scenario modeling and algorithmic solutions, primarily encompassing Quality of Service (QoS) aware VNE, multi-layer cross-domain heterogeneous network VNE, dynamic VNE, and problem-solving algorithms for VNE.Both theoretical and practical strategies to address the VNE challenges in integrated space-terrestrial networks were analyzed in depth.Finally, it provided a foresight into future research directions, aim to offer valuable insights for subsequent studies.